2023
DOI: 10.1021/acs.jpcc.2c08568
|View full text |Cite
|
Sign up to set email alerts
|

Charting Ba-Based Double Perovskite Oxides for Visible-Light-Driven Photocatalytic Water Splitting

Abstract: Realizing green hydrogen generation is contingent on developing low-cost, ecofriendly, and viable photocatalysts for water splitting. Using first-principles screening, we filtered out several Ba-based double perovskites (i.e., Ba 2 BB′O 6 ) that are desired for such applications. Detailed chemical and electronic structure analyses reveal that all of the studied double perovskites, despite their disparate compositions, fall into five classes, depending on the orbital occupancy of the B and B′ cations. Of the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 82 publications
1
2
0
Order By: Relevance
“…87 Bazrafshan et al calculated 28 barium-based DPs (Ba 2 BB′O 6 ) with different B and B′ and found their band gaps in the range 0.1–3.4 eV. 39 Our calculated band gaps are in line with these results.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…87 Bazrafshan et al calculated 28 barium-based DPs (Ba 2 BB′O 6 ) with different B and B′ and found their band gaps in the range 0.1–3.4 eV. 39 Our calculated band gaps are in line with these results.…”
Section: Resultssupporting
confidence: 87%
“…36 Ba 2 BB′O 6 is usually referred to as barium-based DP due to the dominating role of Ba in the structure. 37–40 Hossain et al illustrated that when A-sites are substituted with Ba cations, the structure tends to crystallize as a high-symmetry cubic cell with an Fm 3 m space group, emphasizing the elemental character of Ba cations. 37 Kubel et al illustrated the structural differences in M 2 NaIO 6 (M = Ca, Sr, Ba) DPs due to M cations and pointed out the cubic structure for Ba at A sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation